Beyond Festive Peaks: An Empirical Study of Consumer Behaviour to Develop Strategic Marketing Recommendation for Indonesia’s Cordial Syrup Category - Lestri Fajrinia (Publikasi Indonesia, 2026)
Cordial syrup category has been established for a long time in the Indonesian market with high dependency on Ramadhan and Idul Fitri periods. Despite consistently high seasonal marketing investment and strong brand awareness, this category has reached stagnation in consumption rate, indicating that traditional promotion-driven strategies are no longer able to generate sustainable growth. To resolve this challenge, this research was initiated to relook the consumer behaviour of cordial syrup consumers, to deep dive into any untapped insights that can be an opportunity to unlock business growth through consumer-driven activation and/or innovation. The research was conducted using a qualitative research approach through in-depth interviews with a targeted cordial syrup consumer group segment. The interview data collected was analysed with thematic analysis and further synthesized by integrating the results with literature and business context. The research results identify several major themes consisting of emotional, personal, social, cultural, and marketing factors influencing cordial syrup consumption. These factors interact dynamically and shape consumer purchasing decisions. The findings further demonstrate that consumers' expectations have evolved faster than the industry's current marketing strategy. The emerging of healthy lifestyle, greater convenience, creative inspiration, and year-round relevance are the potentially underdeveloped value propositions that can be utilized for a more progressive marketing approach. The most principal keynote is that every product and packaging innovation should be supported with new value creation that can bring consumers to experience better emotional and social fulfilment.